Successful pregnancy in a woman with lymphangioleiomyomatosis: a case report - Pavão,Margarida (2024)
Abstract Lymphangioleiomyomatosis (LAM) is a rare disease that mainly affects women of childbearing age. Literature on pregnancy outcomes in women with LAM is limited. This paper reports a successful pregnancy in a woman previously diagnosed with LAM. Despite experiencing a spontaneous hemorrhage from a pelvic lymphangioleiomyoma, which required emergent embolization at 20 weeks’ gestation, a cesarean was performed at 39 weeks, resulting in a healthy newborn.